2019
DOI: 10.1101/706283
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural correlates of the DMT experience as assessed via multivariate EEG

Abstract: Studying transitions in and out of the altered state of consciousness caused by intravenous (IV) N,N-Dimethyltryptamine (DMT -a fast-acting tryptamine psychedelic) offers a safe and powerful means of advancing knowledge on the neurobiology of conscious states. Here we sought to investigate the effects of IV DMT on the power spectrum and signal diversity of human brain activity (6 female, 7 male) recorded via multivariate EEG, and plot relationships between subjective experience, brain activity and drug plasma … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…Recent empirical research has identified increased entropy or signal diversity as a signature of psychedelic states 149 . Recent neuroimaging studies with magnetoencephalography (MEG) and EEG showed that LSD, psilocybin, and DMT increased the Lempel-Ziv complexity, a measure of signal diversity and approximation to entropy, which correlated with the overall intensity of the psilocybin and DMT-induced psychedelic experience 150 151 . Furthermore, in an fMRI study, LSD increased sample entropy in sensory and some higher-order networks 80 .…”
Section: Functional Network Models Of Psychedelic Statesmentioning
confidence: 99%
“…Recent empirical research has identified increased entropy or signal diversity as a signature of psychedelic states 149 . Recent neuroimaging studies with magnetoencephalography (MEG) and EEG showed that LSD, psilocybin, and DMT increased the Lempel-Ziv complexity, a measure of signal diversity and approximation to entropy, which correlated with the overall intensity of the psilocybin and DMT-induced psychedelic experience 150 151 . Furthermore, in an fMRI study, LSD increased sample entropy in sensory and some higher-order networks 80 .…”
Section: Functional Network Models Of Psychedelic Statesmentioning
confidence: 99%
“…and is rapidly metabolized when administered parenterally. [26] Bufotenin is best known as a toad poison, but has also been isolated from Scheme 1. Overview on l-tryptophan-fed natural product pathways in Psilocybe sp.…”
Section: Pharmacology and Medicinal Chemistrymentioning
confidence: 99%
“…While DMT is known to elicit a psychedelic effect in humans, the compound is not orally active in the absence of monoamine oxidase inhibitors (see also section 2.3.) and is rapidly metabolized when administered parenterally [26] . Bufotenin is best known as a toad poison, but has also been isolated from Anandenanthera trees (legumes), and from the mushroom Amanita citrina (false death cap).…”
Section: L‐tryptophan‐derived Natural Products In Psilocybe Speciesmentioning
confidence: 99%
“…However, the interviewer needs to be highly trained in the interviewing technique to ensure reliability. Microphenomenology has been used to study awe Stepanova et al, 2019), meditative experiences (Petitmengin et al, 2017;Prpa et al, 2018;Przyrembel and Singer, 2018), and altered states of consciousness caused by DMT-a fast-acting tryptamine psychedelic (Timmermann et al, 2019). Both phenomenology and microphenomenology can be useful in describing self-transcendence, but which one you use depends on if you want to study the experience generally and across life times (phenomenology), or if you want to look at one specific experience in great detail (microphenomenology).…”
Section: Phenomenological Interviewsmentioning
confidence: 99%